Pengaruh Jarak Tanam Terhadap Pertumbuhan dan Hasil Tanaman Bayam (Ammaranthus tricolor) Secara Hidroponik NFT (Nutrient Film Technique) - I Made Suarjana; I Gusti Ngurah Apriadi Aviantara; Gede Arda (Program Studi Teknik Pertanian, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2020)
The purpose of this study was to determine the effect of spacing on the growth and yield of spinach plants with hydroponic NFT (Nutrient Film Technique) and to determine the most effective spacing and spinach results of hydroponic NFT plant growth. This study uses a Completely Randomized Design (CRD) consisting of four treatment spacing, namely 5 cm, 10 cm, 15 cm and 20 cm. Each treatment uses the same number of plants as 15 plants in one gutter. The study was conducted for 20 days. The parameters observed were plant height, number of leaves, fresh weight, dry weight, root length, and stem diameter. High parameters and number of leaves are measured every two days, while parameters of fresh weight, dry weight, root length, and stem diameter are measured after harvest on the 20th day. For the final value obtained from the calculation of plant height growth parameters, namely JT5 (27.45), JT10 (32.45), JT15 (33.22), and JT20 (32.94). And for the final value obtained from the calculation of the number leaf growth parameters, namely JT5 (11.21), JT10 (12.19), JT15 (12.51), and JT20 (12.17). While the final value of crop yield parameters for root lengths is JT5 (28.06), JT10 (30.43), JT15 (31.36), JT20 (30.70). For the stem diameter the average value obtained is JT5 (0.72), JT10 (8.84), JT15 (0.90), JT20 (0.85). For fresh weight of plants, the average values ??obtained are JT5 (182.40), JT10 (208.24), JT15 (215.07), JT20 (210.76). And for dry weight, the average value obtained is JT5 (9.51), JT10 (13.52), JT15 (15.05), JT20 (13.71). It can be concluded that from the results of the ANOVA analysis, the treatment of 15 cm spacing had the best results and the spacing of 5 cm showed the lowest results in each treatment observed.